Tren dan Perkembangan Fashion Syariah Pada Era Modern di Kota Bandung - Srisusilawati, Popon; Prasetyo, Salma Nabila; Nur Hamidah, Siti Aulia; Rihhadatull 'Aisy, Raisa Adila; Oktavia, Reza (ITB AAS INDONESIA Surakarta, 2024)
At this time the halal industry in Indonesia is becoming a public concern, especially in the field of fashion. The development of fashion trends cannot be separated from the existence of increasingly trendy technology, so business actors are trying to take advantage of these technological developments as a means of ideas and innovations to create products that are appropriate for their time in order to attract the attention of consumers and be able to compete in the market. With the development of syar'i fashion trends, resulting in the increase in sharia business, many designers continue to be innovative by bringing up many designs that are in demand by the public. This study aims to determine the trend of sharia fashion in the modern era in the city of Bandung, as well as find out how far the development of sharia fashion in the modern era. The research method used is qualitative with a descriptive analysis approach by collecting data sourced from previous research, obtained through Google scholar and dimensions. The results of this study show that the halal industry in the fashion sector has become a trend and has a very big opportunity to develop the halal fashion sector. However, behind the great opportunities there are challenges that must be faced including: Lack of halal awareness in Indonesian society, Lack of Public Understanding of the Concept of Halal in Fashion, not many fashion MSMEs that take care of halal certification, low awareness of the Indonesian people to compete.